2021
DOI: 10.3389/fmed.2021.774487
|View full text |Cite
|
Sign up to set email alerts
|

Achieving WHO's Goal for Reducing Cesarean Section Rate in a Chinese Hospital

Abstract: Background: To address the worldwide dramatically increased Cesarean section (CS) rate in the past decades, WHO has recommended the CS rate should not be higher than 10–15%. Whether it is achievable remains unknown.Methods: We collected the data of delivery from 2008 to 2017 in two typical regional hospitals in China: Longhua Hospital (national policies rigorously implemented) and Dongguan Hospital (national policies not rigorously implemented). We compared between the two hospitals the 10 years trend in annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although studies from Jordan and Turkey show that refugees have higher cesarean rates, our study found higher in Turkish mothers [21,22]. This is consistent with the worldwide increased rate of cesarean sections over the last decades, which is much beyond the WHO recommendation of 10-15% [23].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although studies from Jordan and Turkey show that refugees have higher cesarean rates, our study found higher in Turkish mothers [21,22]. This is consistent with the worldwide increased rate of cesarean sections over the last decades, which is much beyond the WHO recommendation of 10-15% [23].…”
Section: Discussionsupporting
confidence: 88%
“…Although studies from Jordan and Turkey show that refugees have higher cesarean rates, our study found higher in Turkish mothers [ 21 , 22 ]. This is consistent with the worldwide increased rate of cesarean sections over the last decades, which is much beyond the WHO recommendation of 10-15% [ 23 ]. Higher medico-legal anxiety and a history of a cesarean section could explain why Turkish mothers have a higher number of cesarean sections.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the success rate of vaginal delivery induced by a balloon was about 70%, higher than reported in the literature [ 14 , 34 37 ]. The high success rate of TOLAC in our research may be related to doctor’s experience (i.e., obstetric department director), who was personally very supportive of vaginal birth, trained the team well, and promoted the use of midwifery techniques, which resulted in the absence of complications in most of the induced labor pregnant women [ 38 ]. In their study, Dodd et al reported that 68% of pregnant women with previous CS were willing to accept IOL [ 39 ], as it could help avoid unnecessary repeated CS and improve the success rate of vaginal delivery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%